Styryllactones and bis-styryllactones from the stembark of goniothalamus lanceolatus miq. and their cytotoxic activity / Nur Vicky Bihud - Bihud, Nur Vicky (2020)
In the search for new bioactive compounds from plant of Malaysia, Goniothalamus lanceolatus Miq., an indigenous plant from Sarawak was investigated. This plant is used by the natives as a traditional medicine to treat various illnesses such as cancer, fever and skin diseases. Preliminary cytotoxic screening on the crude extracts against lung and colorectal cancer cell lines showed promising results from all parts with percentage of cell viability of less than 20% at concentration of 100 μg/mL. In view of the interesting ethno-medicinal and biological properties mentioned above, a detailed phytochemical study was conducted to provide scientific data for this plant. This study reported the isolation, structure elucidation, cytotoxic evaluation of pure compounds, and the plausible biogenetic route on the isolated compounds. The isolation and purification of compounds were accomplished by utilizing modern chromatographic techniques such as MPLC, HPLC and recycling HPLC. All structures were established through extensive 1D and 2D NMR analysis, whilst the absolute configurations were established by electronic circular dichroism data (ECD), supported by NOESY experiments and data comparison with literature values. Twelve styryllactones were isolated and identified as 6S-goniothalamin 1, (6S,7S,8S)- goniodiol 2, (6S,7R,8S)-8-chlorogoniodiol 3, (6S,7S,8S)-goniodiol-7-monoacetate 4, (6S,7S,8S)-goniodiol-8-monoacetate 5, (6S,7S,8S)-(-)-ent-isogoniothalamin oxide 6, (1S,5S,7R,8R)-3-endo, 7-endo-(-)-9-deoxygoniopypyrone 7, (1S,5S,7S,8R)-3-exo, 7- exo-(+)-deoxygoniopypyrone B 8, (1S,5S,7R,8S)-3-endo, 7-endo-(-)-8-epi-9- deoxygoniopypyrone 9, (1S,5S,7R,8S)-3-exo, 7-endo-(+)-8-epi-9- deoxygoniopypyrone 10, (1S,5S,7R,8S)-3-endo, 7-endo-(-)-8-epi-9- deoxygoniopypyrone acetate 11 and (1S,5S,7S,8S)-(-)-goniofupyrone B 12. Interestingly, the styryllactones isolated from this plant possessed an α,β-unsaturated δ-lactone moiety with a 6S configuration, and δ-lactone moiety with a 1S configuration, which were a rare occurrence from nature. With the exception of 10, all compounds are reported for the first time from the genus Goniothalamus. Seven new bis-styryllactones, named goniolanceolatins A-H 13-19 were also described. These goniolanceolatins comprised of either a pyranopyrone unit and a styrylpyrone unit, or two styrylpyrone units, which are linked by an ether bridge at positions C-8/C-8', C- 8/C-7', or C-7/C-8'. The new compounds 13-19 were evaluated for their cytotoxicity against series of human lung and colorectal cancer cell lines, which revealed a promising cytotoxicity for 14 and 16 with IC50 values ranging from 2.2 to 7.8 μM, while sparing the human non-cancerous lung and colorectal cells. Docking studies of the active compounds 14 and 16 showed that they were able to bind with EGFR tyrosine kinase and cyclin-dependent kinase 2 through hydrogen bonding interactions with the important amino acids such as Lys721, Met769, Asn818, Arg157, Ile10, and Glu12.